Health literacy and COVID‐19. (16th July 2020) - Spring, Hannah
Abstract: In early 2020, the world experienced an unprecedented health crisis. When the pandemic of coronavirus was declared by the World Health Organization, it brought with it sudden and dramatic changes to everyday life. In the UK, the key message from the Government was to 'Stay at home, protect the NHS, save lives', sending out a clear warning that failing to stay at home would put other lives and the ability of the NHS to cope at risk. This editorial discusses COVID‐19, how society responded and the vital role that health literacy plays in saving lives during a global health emergency.